1976
DOI: 10.1126/science.785599
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Skin Allografts in Mice Treated with Fractionated Total Lymphoid Irradiation

Abstract: Treatment of recipient Balb/c mice with fractionated, high-dose total lymphoid irradiation, a procedure commonly used in the therapy of human malignant lymphomas, resulted in fivefold prolongation of the survival of C57BL/Ka skin allografts despite major histocompatibility differences between the strains (H-2 d and H-2 b , respectively). Infusion of 10 7 (C57BL/Ka × Balb/c)F 1 bone marrow cells after total lymphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 21 publications
0
74
0
Order By: Relevance
“…TLI results in thymus-derived (T) lymphocytopenia as well as impairment of T cell functions including elimination of the in vitro responsiveness to phytohemagglutinin and the in vitro reactivity to alloantigens in a one-way mixed lymphocyte reaction. The in vivo correlate was prolonged survival of strongly histoincompatible skin and perfused heart allografts in mice and rats (13,14,17). The immunosuppressive effects of TLI in man were studied in patients who had undergone radiotherapy for Hodgkin disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TLI results in thymus-derived (T) lymphocytopenia as well as impairment of T cell functions including elimination of the in vitro responsiveness to phytohemagglutinin and the in vitro reactivity to alloantigens in a one-way mixed lymphocyte reaction. The in vivo correlate was prolonged survival of strongly histoincompatible skin and perfused heart allografts in mice and rats (13,14,17). The immunosuppressive effects of TLI in man were studied in patients who had undergone radiotherapy for Hodgkin disease.…”
Section: Resultsmentioning
confidence: 99%
“…2). At The long-lasting potent immunosuppressive effects of TLI have been well established in all animals studied so far (mice, rats, and dogs) including man (13)(14)(15)(17)(18)(19). TLI results in thymus-derived (T) lymphocytopenia as well as impairment of T cell functions including elimination of the in vitro responsiveness to phytohemagglutinin and the in vitro reactivity to alloantigens in a one-way mixed lymphocyte reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the search for minimal myeloablative and/or immunosuppressive treatments that allow long-term engraftment of the transduced HSC in the recipients is urgently required for the development of stem cell gene therapies for non-malignant diseases. 6,7 In the late 1970s, Slavin et al 8,9 showed that chimerism induced by infusion of allogeneic marrow after total lymphoid irradiation was associated with tolerance to skin grafts of the same donor type. More recent evidence suggests that stable mixed hematopoietic chimerisms can be induced in non-myeloablated animals receiving only immunosuppression before the infusion of allogeneic HSC [10][11][12] or by increasing the number of cells transplanted.…”
Section: Gene-expressing Cells Were Found In the Grafted Hematopoietimentioning
confidence: 99%